Anna, Banana, and the little lost kitten - Rissi, Anica Mrose (Rissi, Anica Mrose. Anna, Banana, 2017)
When third grader Anna's first attempt to rescue a lost kitten ends in disaster because her dog Banana scares the kitten away, Anna realizes that she needs the help of her family and friends to catch the lost kitten and find it a good home.